2002
DOI: 10.17221/4389-pse
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and chemical composition of wood tissues of short rotation willow coppice cultivated on arable land

Abstract: In the period 19961999 field trial was performed in Obory near Kwidzyn on heavy textured Fluvisols. The experiment was aimed to determine yield, chemical composition, heat value of wood of six genotypes of willow coppice in relation to cutting frequency and on determining the costs and profitability of willow production on arable land for purposes of energy generation. Yield of wood dry matter in one-year cutting cycle amounted to 14.09 t.ha 1 .year 1 and significantly increased to 16.05 and 21.55 t.ha 1 .year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
2
15
2
Order By: Relevance
“…These values were in accordance with the values from our previous studies [7,9], and with the values obtained by Szczukowski et al [26], and Tharakan et al, [27], approx. 19 MJ/kg.…”
Section: Resultssupporting
confidence: 93%
“…These values were in accordance with the values from our previous studies [7,9], and with the values obtained by Szczukowski et al [26], and Tharakan et al, [27], approx. 19 MJ/kg.…”
Section: Resultssupporting
confidence: 93%
“…The average willow yield reported from experimental areas in Poland ranged from 10 to 12 Mg ODM ha À1 year À1 (Faber and Kuś, 2007;Kuś et al, 2008;Stolarski, 2009;Szczukowski et al, 2002;Tworkowski et al, 2006). The yield reported for regular plantations is generally lower and ranges from 4 to 10 Mg ODM ha À1 year À1 .…”
Section: Discussionmentioning
confidence: 99%
“…Aylott et al (2008) reported average dry matter yields for different poplar and willow clones of 4.9-10.7 Mg DM ha -1 year -1 using data from a 49-site SRC yield trial network in the UK. For different willow clones in northern Poland, Szczukowski et al (2002) reported average growth increments between 14.2 and 21.7 Mg DM ha -1 year -1 . Other authors reported between 6 and 12 Mg DM ha -1 year -1 for willow and poplar on average fertile soils in eastern Germany (Bemmann et al 2007;Scholz et al 2004;Werner et al 2004).…”
Section: Woody Biomass Production In Short Rotation Coppicesmentioning
confidence: 99%